A Compensatory Control Account of Meritocracy - Chris Goode; Lucas A. Keefer; Ludwin E. Molina (Journal of Social and Political Psychology, 2014)
Why are people motivated to support social systems that claim to distribute resources based on hard work and effort, even when those systems seem unfair? Recent research on compensatory control shows that lowered perceptions of personal control motivate a greater endorsement of external systems (e.g., God, government) that compensate for a lack of personal control. The present studies demonstrate that U.S. citizens’ faith in a popular economic ideology, namely the belief that hard work guarantees success (i.e., meritocracy), similarly increases under conditions of decreased personal control. We found that a threat to personal control increased participants’ endorsement of meritocracy (Studies 1 and 2). Additionally, lowered perceptions of control led to increased feelings of anxiety regarding the future, but the subsequent endorsement of (Study 2) or exposure to (Study 3) meritocracy attenuated this effect. While the compensatory use of meritocracy may be a phenomenon unique to the United States of America, these studies provide important insight into the appeal and persistence of ideologies in general.